Entender la ciudad - Echeñique, Marcial (Revista EURE - Revista de Estudios Urbano Regionales, 2014)
Today most of us live in the shadow of vast metropolises which extend over hundreds of kilometers, dominating our existence. Wherever we happen to live, we face similar problems: congestion on the roads and over-crowding on land, decaying centres and segregation on the outskirts; violence and social problems in the old areas and environmental disturbance in the new. All of this gives rise to theories which explain why these things happen and which also be usefil in the search for world-wide solutions. This article presents such a theory -an approach to understanding how cities work and how they develop through time. As such it is more akin to the study of biological organisms which constantly adapt to change, than to the static artifacts perceived by architects and engineers. The development of computers has made it possible to model, that is to represent, the uniqueness to each city as expressed through its streets and buildings and, using economic theories, to view the city as a market which responds to changing prices. Change in the city is largely brought about by the evolution of technology, particularly in transport and communications. Change also occurs as a result of government intervention, in the form of infrastructure investment, regulation and fiscal policies. Such measures can be simulated by computer and their economic, social and environmental impacts evaluated. The article concludes with examples of models in use in London and Santiago. London is a city in a highly developed country -its growth is slow but in internal structures undergoing change. Santiago is a city in a country of rapid growth which offers opportunities for guiding development towards a more efficient, more just and better environment for living. Í 